Improving Students’ Speaking Skills Through YouTube Videos at the Seventh Grade OF MTs N 02 Bengkulu - Syaputra A.Y; Azwandi Azwandi; Syafryadin Syafryadin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Speaking is a skill which deserves attention every bit as much as literary skills, in both first and second language. The aims of this study were to discover (1) improving students' Speaking skills through YouTube Digital Videos at seventh grade stuednts of MTsN 02 Kota Bengkulu, (2) Some factors influence how students' Speaking skills changes after using YouTube digital videos at seventh grade students of MTsN 02 Kota Bengkulu. This Classroom Action Research (CAR) project included 36 students of the seventh grade students of MTsN 02 Kota Bengkulu. The researcher investigated the enhancement of students' speaking skills and the factors that influence the change of students' speaking skills using quantitative and qualitative data. This study's instruments included a speaking test, an observation checklist, field notes, and an interview. The results of the research were described as follow: (1) the improving of students' speaking skills through YouTube digital videos was based on the test results. the research was declared successful the mean score on the students' speaking test was 77. The aforementioned statistics allowed us to determine that the mean speaking score for students was 77, meaning that eighty five percents of students were good and very good. In this study, 42% of students, or 15 students, were good speakers, whereas 45% of students, or 16 students, were very good speakers, (2) factors that influence how students' speaking skills changes after using YouTube digital videos were motivation and students’ activeness in following the learning process by viewing the YouTube digital videos. The results of the research can be concluded that YouTube digital videos can improve students’ speaking skills and it was affected by motivation, the students’ factors and the teacher’s cooperation in applying the YouTube digital media. Keywords: Classroom Action Research (CAR), Speaking skills, YouTube Digital Videos